A leitura dialógica com ressignificação valorada do livro e do filme Shrek na sala de aula - Cardoso, Mari Geralda D’Avila (2024)
This research investigates the possibilities of ethical and discursive reading in schools, focusing on active comprehension activities of the book Shrek, by William Steig, published in 1990, and its first film adaptation, directed by Andrew Adamson and Vicky Jenson, in 2001, by the animation studio Dream World. The study makes use of the categories satire, parody, grotesque and sublime, which support Bakhtin's proposed analysis of carnivalization. By applying the categories of analysis to the dialogical reading of Shrek, we intend to observe how the different voices of these artistic-literary creations (author, characters, social voices) enter dialogue with traditional fairy tales and the worldview of contemporary society. This research analyzes the application of a didactic proposal for a literary reading path with valued resignification developed by Carvalho (2021, 2023, 2024), in order to explore the capacities for producing meaning in the ethical-aesthetic-discursive plane in a 9th grade elementary school class. Our central hypothesis is that the procedures for understanding dialogic reading activities from na ethical-stylistic-discursive perspective have a significant role in the formation of the reader, offering possibilities of didactic mediation in the classroom that help to problematize the construction of meaning in statements and expand the student’s critical ability. Therefore, this research, within the field of Applied Linguistics, carries out a case study that explores the valued reinterpretation of Shrek, both in its literary and cinematographic form, in opposition to the values advocated by traditional fairy tales. From the perspective of responsive and responsible understanding, the research participants contrast the traditional values of fairy tales with the values assumed by the works analyzed through ethical-discursive reading procedures. In this way, the research presents and analyzes, in an empirical situation, the application of dialogic reading work in a 9th grade class of Elementary School II at a state school located in the city of Aracaju, Sergipe. In this research, the categories of carnivalization outlined by Bakhtin (2011) are explored in a dialogic reading workshop, having as a product a pedagogical notebook that provides theoretical and practical support for reading proposals that follow the same parameter.